EXPLORING THE COMPATIBILITY OF SHARIA LAW AND DEMOCRATIC VALUES IN INDONESIA'S DEMOCRACY - Imam Hanafi; Redi Yana Kapisa; Ayi Maulana; Adi Mursalin; Muhammad Nurhisyam Ali Setiawan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This study explores the compatibility of Sharia law and democratic values in the context of Indonesia's democracy. It examines the interplay between religious traditions and democratic principles, focusing on the legal framework, societal dynamics, and challenges in balancing Sharia law with democratic governance. The study analyzes the constitutional recognition of Islam as the majority religion while upholding democratic principles, the protection of human rights and gender equality, the implementation of Sharia-inspired regulations at the local level, and the role of public opinion in shaping the compatibility between Sharia law and democratic values. Through a qualitative research approach, including interviews, document analysis, and a review of existing literature, this study comprehensively analyzes the complexities and possibilities of reconciling religious traditions with democratic governance in Indonesia. The findings contribute to academic discourse, inform policymakers, and offer insights for promoting inclusive and democratic governance in Indonesia and other contexts with significant Muslim populations.